Biochar and activated carbons preparation from invasive algae Sargassum spp. for Chlordecone availability reduction in contaminated soils. Issue 4 (August 2021) - Ranguin, Ronald; Delannoy, Matthieu; Yacou, Christelle; Jean-Marius, Corine; Feidt, Cyril; Rychen, Guido; Gaspard, Sarra
Abstract: This work aims to valorize an invasive brown macroalga (Sargassum spp . consisting of two species Sargassum fluitans and Sargassum natans ) by producing biochars (BCs) and activated carbons (ACs). Its abundant and frequent occurrence along the Caribbean coastlines, Florida, Gulf of Mexico during the last past nine years, have triggered human health concerns and have negatively impacted local economy, ecology and the environment. In this paper, BCs and ACs were developed to assess the reduction of chlordecone (CLD) environmental availability in artificial and tropical contaminated soils. Such innovative approach was proposed to limit CLD bio-availability to fauna and outdoor reared-animals. The BCs were prepared by pyrolysis at 700 °C while ACs samples by chemical or physical activation. Textural characterization, has evidenced that bi-modal structures with micro- and mesopores, various surface and high pore volumes were successfully obtained. Finally, the environmental availability tests resulted in various ability of BCs or ACs to significantly sequestrate CLD on artificial contaminated soils and on a natural nitisol. In particular, the BCs prepared with a 3 h pyrolysis time, exhibited the highest porosities properties and was the best candidate to efficiently sequestrate CLD in soil samples. Graphical Abstract: ga1